Євроінтеграція та використання інноваційних технологій у процесах публічного управління (на прикладі Виконавчого комітету Стрийської міської ради) - Хомин, Анна Василівна; Khomyn, Anna Vasylivna (Національний університет "Львівська політехніка", 2023)
У сучасному світі впровадження євроінтеграційних процесів та використання інноваційних технологій у публічному управлінні є актуальним завданням для багатьох країн, які прагнуть до розвитку та підвищення ефективності своїх систем управління. В контексті цієї проблематики особливо важливою стає аналіз та оптимізація діяльності місцевих органів влади, оскільки саме на місцевому рівні здійснюється багато сфер державного управління, що безпосередньо впливає на якість життя громадян. Метою роботи є виявлення проблемних аспектів у діяльності Виконавчого комітету Стрийської міської ради, аналіз сучасного стану публічного управління на місцевому рівні та розробка рекомендацій щодо вдосконалення цієї діяльності з використанням євроінтеграційних процесів та інноваційних технологій. Об'єктом дослідження є Виконавчий комітет Стрийської міської ради як представник місцевої влади, діяльність якої напряму впливає на життя місцевого населення. У першому розділі було розкрито поняття та сутність євроінтеграції, її переваги та виклики для публічного управління. Охарактеризовано можливості та переваги використання інноваційних технологій в публічному управлінні. Проаналізовано нормативно-правове регулювання в контексті євроінтеграції та використання інноваційних технологій. У другому розділі дано загальну характеристику діяльності Виконавчого комітету Стрийської міської ради. Проведено аналіз виробничо-господарської діяльності та фінансового стану Виконавчого комітету. Оцінено рівень євроінтеграційних процесів та використання інноваційних технологій в управлінні в місцевій владі.Визначено проблеми в реалізації євроінтеграційних ініціатив та впровадженні інноваційних технологій. Далі було розроблено рекомендації щодо удосконалення публічного управління у Виконавчому Комітеті Стрийської Міської ради в контексті євроінтеграції та інноваційного розвитку. Запропоновано конкретні заходи щодо адаптації до стандартів ЄС та імплементації європейських практик. Наведено приклади країн ЄС, які успішно інтегрували та використовують цифрові технології в публічному управлінні. Перший проектний захід спрямований на підвищення доступності та якості публічних послуг. Громадяни та бізнес зможуть отримувати послуги онлайн, без необхідності особисто звертатися до органів влади. Це економить час та ресурси, а також робить послуги більш зручними та доступними. Другий рекомендаційний захід передбачає визначення кращих практик та порівняння показників різних органів місцевого самоврядування дозволяє визначити, які з них працюють найефективніше. Третій пропонований захід спрямований на, підвищення довіри до влади. Прозорість, підзвітність та боротьба з корупцією роблять владу більш підзвітною перед громадянами, що призводить до зростання довіри до неї. Четвертий пропонований захід спрямований на спрощення та оптимізація процедур спрямовані на, економію часу та ресурсів. Громадяни та бізнес зможуть отримувати послуги швидше та дешевше, а органи влади зможуть краще використовувати свої ресурси. Рекомендації та заходи відіграють ключову роль у модернізації публічного управління, підвищенні ефективності децентралізації, стимулюванні економічного розвитку, посиленні євроінтеграційних прагнень України, зміцненні демократії та верховенства права, а також у покращенні рівня життя громадян. Їх впровадження потребуватиме значних зусиль та ресурсів, але це інвестиція в майбутнє України, яка допоможе країні стати більш демократичною, процвітаючою та європейською.Виконавчий комітет Стрийської міської ради, рекомендації, адаптація до стандартів ЄС, імплементація європейських практик, цифрові технології.

In today's world, the implementation of European integration processes and the use of innovative technologies in public administration is an urgent task for many countries that seek to develop and improve the efficiency of their management systems. In the context of this issue, it is especially important to analyze and optimize the activities of local authorities, since it is at the local level that many areas of public administration are carried out, which directly affects the quality of life of citizens. The purpose of the study is to identify problematic aspects in the activities of the Executive Committee of the Stryi City Council, to analyze the current state of public administration at the local level and to develop recommendations for improving these activities using European integration processes and innovative technologies. The object of the study is the Executive Committee of Stryi City Council as a representative of local authorities, whose activities directly affect the lives of the local population. The first section describes the concept and essence of European integration, its benefits and challenges for public administration.The opportunities and benefits of using innovative technologies in public administration are characterized.The regulatory framework in the context of European integration and the use of innovative technologies is analyzed. The second section provides a general description of the activities of the Executive Committee of Stryi City Council. The analysis of production and economic activities and financial condition of the Executive Committee is carried out. The level of European integration processes and the use of innovative technologies in local government management is assessed. Problems in the implementation of European integration initiatives and the introduction of innovative technologies are identified. Further, recommendations were developed to improve public administration in the Executive Committee of Stryi City Council in the context of European integration and innovative development. Specific measures to adapt to EU standards and implement European practices are proposed. Examples of EU countries that have successfully integrated and used digital technologies in public administration are given. The first project activity is aimed at improving the accessibility and quality of public services. Citizens and businesses will be able to receive services online without having to contact the authorities in person. This saves time and resources, and makes services more convenient and accessible. The second recommended measure involves identifying best practices and comparing the performance of different local governments to determine which ones work most effectively. The third proposed measure is aimed at increasing trust in the authorities. Transparency, accountability, and the fight against corruption make the authorities more accountable to citizens, which leads to increased trust in them. The fourth proposed measure is aimed at simplifying and optimizing procedures to save time and resources. Citizens and businesses will be able to receive services faster and cheaper, and the authorities will be able to make better use of their resources. The recommendations and measures play a key role in modernizing public administration, increasing the effectiveness of decentralization, stimulating economic development, strengthening Ukraine's European integration aspirations, strengthening democracy and the rule of law, and improving the living standards of citizens. Their implementation will require considerable effort and resources, but it is an investment in Ukraine's future that will help the country become more democratic, prosperous, and European.
European integration and the use of innovative technologies in the processes of public administration (on the example of the Executive Committee of the Stryi City Council)
Keywords: 6.281.00.00; євроінтеграція; публічне управління; інноваційні технології; European integration; public administration; innovative technologies; Executive Committee of Stryi City Council; recommendations; adaptation to EU standards; implementation of European practices; digital technologies. List of used literature sources 1. N. Volkova Strategic management of public service personnel in the context of European integration - 2023 - 5 p. - https://orcid.org/0000-0003-0795-9778 2. I.Moskalets The role of innovations in improving the efficiency of public administration - 2024 - 16 pp. - https://journals.indexcopernicus.com/api/file/viewByFileId/1851870 3. Document flow and information and communication processes in the activities of local authorities. Document; Information; Text in the Modern Social Space: Problematic Fields of Development: Proceedings of the X All-Ukrainian Scientific and Practical Internet Conference (Lviv; November 8-9; 2023). Ukrainian Academy of Printing; Department of Information; Library and Archival Affairs. Lviv: UAP; 2024. С. 46-50. 4. Transformation of legal systems is a fundamental condition for sustainable development. Information and Law. 2023. No. 2 (45). С. 9 -32. DOI: https://doi.org/10.37750/2616-6798.2023.2(45).2823122. 5. Institutionalization of the digital economy: contradictions and directions of their solution. Economic theory and law. 2021. No. 1 (44). С. 25-28